Physical and Chemical Characterization of Silica Based Raw Materials from Industrial Waste - Palaniandy, Samayamutthirian; Nizar Ismail, Khairul; Azizi Mohd Azizli, Khairun (Malaysian Journal of Science, 2002)
Silica sand and Pulverised Fuel Ash (PFA) is considered as silica based waste materials and it have variety of usage depending on its particle size and purity. Value adding of these raw materials will enhance the exploitation of these materials in various industries. The physical and chemical properties of these materials are essential that it will determine the utilization of these materials. The phase analysis, chemical composition, particle size distribution and the morphology of the materials were determined to investigate the appropriate utilization of these raw materials in various applications. Local PFA is considered class F and has various applications as construction materials.